Non-classical roles of bacterial siderophores in pathogenesis - Arnold, Elliot (Frontiers in Cellular and Infection Microbiology, 2024)
Within host environments, iron availability is limited, which instigates competition for this essential trace element. In response, bacteria produce siderophores, secondary metabolites that scavenge iron and deliver it to bacterial cells via specific receptors. This role in iron acquisition contributes significantly to bacterial pathogenesis, thereby designating siderophores as virulence factors. While prior research has primarily focused on unravelling the molecular mechanisms underlying siderophore biosynthesis, uptake, and iron sequestration, recent investigations have unveiled additional non-iron chelating functions of siderophores. These emerging roles are being consistently shown to support bacterial pathogenesis. In this review, we present the current understanding of siderophores in various roles: acquiring non-iron metal ions, supporting tolerance to metal-induced and reactive oxygen species (ROS)-induced stresses, mediating siderophore signalling, inducing ROS formation, and functioning in class IIb microcins. By integrating recent findings, this review aims to provide an overview of the diverse roles of siderophores in bacterial pathogenesis.